UI/UX Design for E-Commerce For Sesaot Village Using Figma and the User-Centered Design (UCD) Method - Rifqi Sulthon Abqari; Hendri Purnomo; Bayu Wibisana; Rahmanto, Krisostomus Nova; Grendis, Nuraqilla Waidhah Bintang (CV. Abhinaya Indo Group, 2025)
The swift expansion of e-commerce demands accessible digital platforms; nevertheless, numerous current applications lack intuitiveness, leading to an unsatisfactory user experience. This study creates a UI/UX for an online shopping platform utilizing Figma and the User Centered Design (UCD) approach to fulfill user requirements. This research aims to offer a structured method for creating e-commerce interfaces that improve user satisfaction. The techniques employed consist of user research, specification of requirements, development of prototypes, and testing for usability. The outcome is a model of an e-commerce site featuring a user-friendly interface that showcases an impressive System Usability Scale (SUS) score. Users mentioned a greater simplicity in usage and contentment, suggesting the success of the UCD method. In summary, utilizing UCD with Figma effectively created an interface that fulfills user requirements and boosts engagement.